Solvent design for post combustion chemical absorption process - Ahmad, M. Z. (Elsevier B.V., 2016)
Post combustion, chemical absorption process is one of the most matured technologies to capture CO2 from large point emission sources. This technology can easily retrofitted to any existing power plant and highly selective with very high carbon capture efficiency at low CO2 concentration and low pressure. However, the big barriers to commercialize this technology at large scale area are due to high energy penalty, high investment cost and can cause environmental impact. In this work an integrated molecular and process level is used to develop a systematic framework for design of liquid solvent for chemical absorption, Post Combustion Carbon Capture process using Computer Aided Molecular Design (CAMD) approach. The proposed solvent candidates are generated using reverse design approach where solvents that match the target properties are identified. The methodology for this work consists of four steps: 1) Problem formulation, 2) Generation of single liquid solvent candidate using ICAS software, 3) Prediction of reaction between potential solvent candidate and CO2 based on amines functional group and 4) Evaluation on process performance by calculating heat required for solvent regeneration process. Preliminary result of this study reveal that 25 solvent candidates for chemical absorption process have successfully been generated from amine and alcohol functional group.